2008
DOI: 10.1111/j.1740-0929.2008.00555.x
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition, palatability and physical characteristics of venison from farmed deer

Abstract: The quality of venison from farmed deer were evaluated based on chemical composition, palatability scores, W-B shear force, ultimate pH, and color. The samples of venison were derived from javan rusa (Cervus timorensis russa), moluccan rusa (Cervus timorensis moluccensis), sambar (Cervus unicolor brookei), fallow (Dama dama) and imported red deer (Cervus elaphus). Moluccan rusa and red deer were fed grass. Javan rusa, sambar and fallow deer were fed concentrate. The venison obtained from grazing deer (grass-fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 10 publications
1
11
2
Order By: Relevance
“…The supraspinatus muscle characterized with the highest pH, which may lead to conclusion about the development of DFD-like lower meat quality. Opposite to results of Bykowska et al (2018), Dahlan and Norfarizan-Hanoon (2008) did not observe any significant differences in the pH value of the analyzed muscles (musculus longissimus dorsi, psoas major, and biceps femoris). According to Bykowska et al (2018), the fallow deer muscles also differed with the temperature measured in the early postmortem period.…”
Section: Muscle Typecontrasting
confidence: 86%
See 2 more Smart Citations
“…The supraspinatus muscle characterized with the highest pH, which may lead to conclusion about the development of DFD-like lower meat quality. Opposite to results of Bykowska et al (2018), Dahlan and Norfarizan-Hanoon (2008) did not observe any significant differences in the pH value of the analyzed muscles (musculus longissimus dorsi, psoas major, and biceps femoris). According to Bykowska et al (2018), the fallow deer muscles also differed with the temperature measured in the early postmortem period.…”
Section: Muscle Typecontrasting
confidence: 86%
“…Analysis of chemical composition shows that the longissimus thoracis et lumborum had the highest content of dry matter and crude protein and lowest water/protein ratio compared with musculus supraspinatus and semimembranosus (P ≤ 0.0001). Dahlan and Norfarizan-Hanoon (2008) observed higher water, fat, and ash content in musculus biceps femoris compared with musculus psoas major and longissimus dorsi (P ≤ 0.05). Dahlan and Norfarizan-Hanoon (2007) reported that musculus biceps femoris from fallow deer had highest cholesterol content compared with muscle longissimus dorsi (115.83 vs. 103.17 mg 100 g −1 ).…”
Section: Muscle Typementioning
confidence: 82%
See 1 more Smart Citation
“…The majority of the research regarding pH of muscle has been done with regard to DFD and PSE in beef and pork. Although some research has been done on the effect of pH on the color of venison (Macdougall et al, 1979;Rincker et al, 2006;Wiklund et al, 2006;Farouk et al, 2007;Dahlan and Norfarizan Hanoon, 2008), bison (Dhanda et al, 2002, Dhanda et al, 2003 and game meat (Hoffman et al, 2009b;Hoffman and Laubscher, 2010), only limited literature is available with regard to its effect on color stability. Furthermore, the aforementioned studies, which included the relationship of color and pH in game meat, bison, and venison, have generally been part of broader investigations on meat quality and were not specifically focused on this relationship.…”
Section: Ultimate Ph Of Meatmentioning
confidence: 99%
“…The difference between the moisture content in muscle of analysed species was low in the our experiment. Dahlan and Norfarizan Hanoon (2008) states that venison of fallow deer has 74.26% content of moisture in Musculus longisimus dorsi. It can conclude, that the values of moisture are not very different in each animal species.…”
Section: Resultsmentioning
confidence: 99%